2015
DOI: 10.3945/jn.114.203091
|View full text |Cite
|
Sign up to set email alerts
|

Tryptophan Catabolism and Vitamin B-6 Status Are Affected by Gender and Lifestyle Factors in Healthy Young Adults

Abstract: In this population of healthy young adults, gender has the largest influence on serum Kyn metabolite concentrations. The significant covariance of Trp with unrelated amino acids suggests that protein intake may be an important consideration in evaluating Kyn metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
46
2
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 50 publications
8
46
2
2
Order By: Relevance
“…16% higher XA serum concentrations are presented in heavy drinkers than never or occasional drinkers [140]. There is no substantial change in Kyn metabolites was observed among smokers [140], although smoking is associated with considerably lower levels of PLP, biologically active form of vitamin B6 [141], a cofactor for KATs and KYNU.…”
Section: Abnormal Kp and Risk Factors For Cvdmentioning
confidence: 99%
See 1 more Smart Citation
“…16% higher XA serum concentrations are presented in heavy drinkers than never or occasional drinkers [140]. There is no substantial change in Kyn metabolites was observed among smokers [140], although smoking is associated with considerably lower levels of PLP, biologically active form of vitamin B6 [141], a cofactor for KATs and KYNU.…”
Section: Abnormal Kp and Risk Factors For Cvdmentioning
confidence: 99%
“…There is no substantial change in Kyn metabolites was observed among smokers [140], although smoking is associated with considerably lower levels of PLP, biologically active form of vitamin B6 [141], a cofactor for KATs and KYNU. KA, an endogenous antagonist for NMDA and α7 nicotinic acetylcholine receptor, is dramatically increased in rat hippocampus, striatum, and frontal cortex, but not in the serum by prolonged (for 10 days) subcutaneous injections or osmotic minipumps of nicotine.…”
Section: Abnormal Kp and Risk Factors For Cvdmentioning
confidence: 99%
“…The subjects for this study have been described previously (14)(15)(16)(17)(18) and consisted of healthy students with Irish grandparents who had attended the University of Dublin, Trinity College, during a 12 mo recruitment period between February 2003 and February 2004. Overall, 3569 students applied; of these, 2524 individuals who had Irish grandparents and had no major medical problems were invited to participate.…”
Section: Methodsmentioning
confidence: 99%
“…A customized food intake questionnaire was used to assess folic acid intake as previously described (14,18). Briefly, the design of the questionnaire allowed an assessment of vitamin supplements and fortified food intake over the previous week and the average over one month by asking participants to recall their fortified food and supplement intake over those 2 time periods.…”
Section: Methodsmentioning
confidence: 99%
“…As mentioned above, there is growing evidence that the incidence of colon diseases is affected by gender difference. Additionally, accumulating studies have suggested the preventive role of dietary B6 on colon diseases and the status of B6 is affected by gender difference (35). Thus, in this study, we hypothesized that gender difference modulates the colon luminal environment, which is dependent upon B6 status.…”
mentioning
confidence: 93%